2003
DOI: 10.4319/lo.2003.48.3.1202
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of migratory behavior of phytoplankton in stratified waters: Effects of halocline strength and light on Tetraselmis sp. (Prasinophyceae) in an artificial water column

Abstract: There is very little information in the literature about how phytoplankton flagellates respond to rapid changes in salinity (e.g., haloclines of different strength). Here we present such data obtained from experiments with Tetraselmis sp. (Prasinophyceae) in a specially designed artificial water column. The experiments were performed with surface salinities varying from 27.4 to 33.4‰, whereas bottom salinities were essentially constant (34.0-34.6‰). Cells were introduced near the bottom. The first stage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…Although swimming is widespread among phytoplankton (Horner et al 1997), its ecological importance has typically been considered primarily in relation to photic migration (Kamykowski et al 1998), physical stratification (Erga et al 2003), or sex (Govoronova and Sineshchekov 2005). Our observations indicate that phytoplankton motility and chemotaxis can significantly increase exposure to nutrient patches, imparting a considerable nutrient advantage to chemotactic cells.…”
Section: Exploitation Of Nutrient Patches By Phytoplanktonmentioning
confidence: 82%
“…Although swimming is widespread among phytoplankton (Horner et al 1997), its ecological importance has typically been considered primarily in relation to photic migration (Kamykowski et al 1998), physical stratification (Erga et al 2003), or sex (Govoronova and Sineshchekov 2005). Our observations indicate that phytoplankton motility and chemotaxis can significantly increase exposure to nutrient patches, imparting a considerable nutrient advantage to chemotactic cells.…”
Section: Exploitation Of Nutrient Patches By Phytoplanktonmentioning
confidence: 82%
“…Therefore, coastal flagellates should have the ability to quickly sense salinity changes and to control swimming patterns. In some flagellates, (Raphidophyceae) and Heterocapsa triquetra (Ehrenberg) F. Stein (Dinophyceae), cessation of upward swimming and a decrease in swimming speed have been observed when they transit a strong halocline in laboratory conditions (Erga et al 2003, Bearon et al 2006, Jephson et al 2011. Some flagellates such as Gyrodinium aureolum Hulburt form a thick bloom in a strong halocline (Bjørnsen & Nielsen 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations have, nevertheless, found that the movements of phytoplanktonic flagellates are often biochemically mediated (Miller and Diehn 1978;Iseki et al 2002) and are usually driven by sensory responses to environmental stimuli such as light (Kessler et al 1992), gravity (Hä der and Lebert 2001), temperature (Kamykowski 1981), chemical gradients (Lee et al 1999;Clegg et al 2004a), and even salinity (Erga et al 2003). Moreover, recent observations indicate that this behavior may be deceptively sophisticated (Kamykowski and Yamazaki 1997;Bearon et al 2004;Clegg et al 2004b).…”
mentioning
confidence: 99%